Kinetic Analysis of the Thermal Decomposition of Polymer-Bonded Explosive Based on PETN: Model-Fitting Method and Isoconversional Method - Trung Toan Nguyen; Duc Nhan Phan; Van Thom Do; Hoang Nam Nguyen (Advances in Materials Science and Engineering)
This work investigates kinetics and thermal decomposition behaviors of pentaerythritol tetranitrate (PETN) and two polymer-bonded explosive (PBX) samples created from PETN (named as PBX-PN-85 and PBX-PP-85) using the vacuum stability test (VST) and thermogravimetry (TG/DTG) techniques. Both model-free (isoconversional) and model-fitting methods were applied to determine the kinetic parameters of the thermal decomposition. It was found that kinetic parameters obtained by the modified Kissinger–Akahira–Sunose method (using non-isothermal TG/DTG data) were close to those obtained by the isoconversional and model-fitting methods that use isothermal VST data. The activation energy values of thermal decomposition reactions were 125.6–137.1, 137.3–144.9, and 143.9–152.4 kJ·mol−1 for PBX-PN-85, PETN, and PBX-PP-85, respectively. The results demonstrate the negative effect of the nitrocellulose-based binder in reducing the thermal stability of single PETN, while the polystyrene-based binder seemingly shows no adverse influence on the thermal decomposition of PETN in our presented PBX compositions.